CeO2C2 Nanoparticles with Oxygen‐Enriched Vacancies In‐site Self‐embedded in Fe, N Co‐doped Carbon Nanofibers as Efficient Oxygen Reduction Catalyst for Zn‐Air Battery†. Issue 23 (8th September 2022) - Zhang, Mingxin; Peng, Hui; Sun, Kanjun; Xie, Xuan; Lei, Xiaofei; Liu, Sitong; Ma, Guofu; Lei, Ziqiang
Comprehensive Summary: Rational design of robust non‐noble electrocatalysts with numerous oxygen vacancies and highly reactive activity for oxygen reduction reaction (ORR) towards Zn‐air batteries is extremely paramount yet challenging. Herein, a novel CeO2 C2 nanoparticles self‐embedded in Fe, N co‐doped carbon nanofibers (CeO2 C2 @Fe‐N‐C) heterostructure catalyst has been prepared by the in‐site dual template assisted electrospinning technique and subsequent high temperature pyrolysis strategy. Thanks to the CeO2 C2 with oxygen‐enriched vacancies and versatile Fe‐N‐C with rich reactive species and high conductivity, CeO2 C2 @Fe‐N‐C catalyst exhibits outstanding catalytic performance in the ORR process, and shows excellent methanol tolerance and cycle stability. In addition, CeO2 C2 @Fe‐N‐C delivers a nearly four‐electron transfer process in the process of oxygen reduction catalysis, providing a fast‐electrochemical kinetic rate, which makes it an efficient air cathode for the Zn‐air battery. Importantly, the Zn‐air battery fabricated with CeO2 C2 @Fe‐N‐C cathode achieves superior performance including large open‐circuit voltage (1.5 V) and high specific capacity (780 mAh·g –1 at 10 mA·cm –2 ) together with superior reversibility and cycling stability, outperforming commercial Pt/C catalyst. The present work introduces a new strategy to design and develop highly active non‐noble catalysts and highlights the synergy from heterostructure in oxygen electrocatalysis for advanced Zn‐air batteries. Abstract : A novel CeO2 C2 nanoparticles self‐embedded in Fe, N co‐doped carbon nanofibers (CeO2 C2 @Fe‐N‐C) catalyst is prepared by the in‐site dual template assisted electrospinning technique and subsequent pyrolysis strategy. CeO2 C2 @Fe‐N‐C catalyst exhibits superior ORR catalytic performance and shows substantial methanol tolerance and cycle stability.